The moralist international : Russia in the global culture wars - Stoeckl, Kristina; Uzlaner, Dmitry (2022)
"Explains the dynamics and mechanisms behind the backlash against sex and gender based human rights in eastern Europe and the Orthodox world and shows how Russia came to assume a leadership role in the global culture wars